2012
DOI: 10.1097/pep.0b013e3182680f19
|View full text |Cite
|
Sign up to set email alerts
|

Weight Status and Gross Motor Skill in Kindergarten Children

Abstract: Clinicians should consider adjusting gross motor expectations for locomotor or stability tasks in young children with obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…The overall description is of boys with obesity who are more likely seen as unsettled, erratic, physical in some peer relationships, and excluded from others. Kindergarten-aged children with obesity are more likely to have poor gross motor skills (e.g., in locomotion and balance; Roberts, Veneri, Decker, & Gannotti, 2012). In addition, developmental coordination disorder is more likely in young children with obesity (Hendrix, Prins, & Dekkers, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The overall description is of boys with obesity who are more likely seen as unsettled, erratic, physical in some peer relationships, and excluded from others. Kindergarten-aged children with obesity are more likely to have poor gross motor skills (e.g., in locomotion and balance; Roberts, Veneri, Decker, & Gannotti, 2012). In addition, developmental coordination disorder is more likely in young children with obesity (Hendrix, Prins, & Dekkers, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Seven (58%) studies found statistically significant inverse association between FMS total score and BMI [18,21,[23][24][25][26][27]. Three of these were classified as high quality [21,23,27].…”
Section: Association Between Fms and Weight Statusmentioning
confidence: 99%
“…Four studies used a product-oriented test for assessing FMS performance [17,18,24,26] and in three of them FMS were significantly inversely associated with weight status estimated using BMI [18,24,26]. None of these were classified as high quality.…”
Section: Association Between Fms and Weight Statusmentioning
confidence: 99%
See 2 more Smart Citations